Manajemen Hubungan Masyarakat dalam Meningkatkan Kepuasan Pelanggan di SD Sekolah Alam Pangandaran - Bela Safitri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
Public Relations plays an important role in building effective communication between schools and stakeholders such as students, parents, teachers and the community. Therefore, this study aims to find out the level of customer satisfaction in SD Sekolah Alam Pangandaran. This study uses qualitative research with a descriptive approach that uses data collection techniques including interviews, observations, documentation, and involving the Principal of Alam Pangandaran School to describing public relations management in improving customer satisfaction at Sekolah Alam Pangandaran. The results of the study showed that the public relations division was active in providing information in various communication channels, and actively involved parents in various activities. Customer satisfaction measurement is carried out through complaints and suggestions and the parents of students are very satisfied with Sekolah Alam Pangandaran.